2011
DOI: 10.1007/s13244-011-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

What influences clinician’s satisfaction with radiology services?

Abstract: AimPACS and teleradiology systems have led to marked changes in the traditional relationship between referring clinicians and hospital radiology departments. The aim of this study was to assess which factors influence clinicians’ satisfaction with modern radiology services.MethodAn Internet-based survey questionnaire was sent to all referring clinicians within a large hospital network.ResultsFifty-eight percent of 316 clinicians responded to the survey. Seventy percent felt PACS installation had improved repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…Some studies have investigated the impact of PACS on patient length of stay. The findings of these studies [ 37 39 ] showed that this system can reduce the duration of patient stay at hospital. However, a previous study [ 40 ] showed that PACS does not affect the patients’ length of stay at hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the impact of PACS on patient length of stay. The findings of these studies [ 37 39 ] showed that this system can reduce the duration of patient stay at hospital. However, a previous study [ 40 ] showed that PACS does not affect the patients’ length of stay at hospital.…”
Section: Discussionmentioning
confidence: 99%
“…& Increased productivity and decreased reporting time, which can impact clinician's and radiologist's satisfaction [18] & Increased time spent with patients, which can impact patient's and radiologist's satisfaction [19]…”
Section: Some Of the Benefits And Outcome Measures To Consider From Tmentioning
confidence: 99%
“…Some studies have reviewed the impact of PACS on the patients' hospital stay time. The findings of these studies [15, 37,38] showed that this system has been able to led to reducing patients' hospital stay time. However, Krave's study in Australia [39] indicated PACS having no effect on the patients' length of stay in hospital.…”
Section: Reducing Hospital-stay Timementioning
confidence: 99%